Phylogenetic relationships of the genus Sibynophis (Serpentes: Colubroidea) - Zaher, Hussam; Grazziotin, Felipe G.; Graboski, Roberta; Fuentes, Ricardo G.; Sánchez-Martinez, Paola; Montingelli, Giovanna G.; Zhang, Ya-Ping; Murphy, Robert W. (Papéis Avulsos de Zoologia, 2012)
We present the results of the first molecular analysis of the phylogenetic affinities of the Asian colubroid genus Sibynophis. We recovered a sister-group relationship between Sibynophis and the New World Scaphiodontophis. Although Liophidium sometimes is associated with these genera, the relationship is distant. Morphological characters that Liophidium shares with Sibynophis and Scaphiodontophis are resolved as homoplasies that probably reflect the similarities of their specialized feeding habits. The traditional subfamily Sibynophiinae is elevated to the family-level, and Scaphiodontophiinae is placed in its synonymy.